Go Green Assistance in Industry to Increase Energy Efficiency and Reduce Waste - Khaman Zahoor; Syamsul Muqorrobin; Wiwin Rifaatul Fauziyah; imam safii; Ubaidillah (Journal of Cross Knowledge, 2024)
This research aims to analyze Go Green Assistance in Industry to Increase Energy Efficiency and Reduce Waste. This assistance is based on case studies. data analysis with development and solving of problems. In conclusion, the implementation of Go Green Assistance in industry is a vital step towards enhancing energy efficiency and minimizing waste generation. By adopting sustainable practices, industries can not only reduce their environmental footprint but also benefit from cost savings, increased competitiveness, and improved corporate social responsibility. The commitment to green initiatives, such as renewable energy adoption, waste reduction strategies, and efficient resource management, can lead to a more sustainable and prosperous future for both businesses and the planet. Embracing these practices will not only contribute to a healthier environment but also pave the way for a more sustainable and economically viable industrial landscape